Prioritizing Policy for the Electric Vehicle Adoption and Production Ecosystem in Indonesia - Sasongko, Triyono Widi; Ciptomulyono, Udisubakti; Wirjodirdjo, Budisantoso; Prastawa, Andhika (International Journal of Energy Economics and Policy, 2025)
Most countries are expanding their programs for electric vehicles as part of an action to reduce greenhouse gas emissions and fossil fuel consumption. In Indonesia, EV development is significantly behind target. Indonesia has specific conditions regarding innovative products in the automotive industry. The majority of automotive users are economy users. Foreign-origin equipment manufacturers dominate the automotive industry, whereas local manufacturers are comparatively less competitive. This study examines the critical policies for EV adoption and the ecosystem in Indonesia. This analysis employs the analytic network process method based on the benefits, opportunities, costs, and risks model. The results show that, in both the short and long term, the top three priorities offer users greater attractiveness in terms of price and charging-station availability, including purchasing incentives, annual tax incentives, and incentives for charging infrastructure providers. In the short term, the following priorities focus on a producer-oriented policy, specifically co-production with local start-ups and EV share-targeted production. In the long term, the priority is to enhance the appeal of EVs by granting them driving privileges, which will continue through co-production with local start-ups to increase local content-based EV production.